High coexpression of CCL2 and CX3CL1 is gender‐specifically associated with good prognosis in soft tissue sarcoma patients. Issue 9 (4th April 2014) - Kehlen, Astrid; Greither, Thomas; Wach, Sven; Nolte, Elke; Kappler, Matthias; Bache, Matthias; Holzhausen, Hans‐Jürgen; Lautenschläger, Christine; Göbel, Steffen; Würl, Peter; Immel, Uta‐Dorothee; Agaimy, Abbas; et al.
<x xml:space="preserve">Abstract</x> Chemokines are involved in both the negative and positive regulation of inflammatory processes, angiogenesis and cancer/cancer stem cell proliferation as well as the chemoattraction of tumor cells to metastatic sites. The aim of this study was to measure the mRNA expression levels of three chemokines, CCL2, CCL7 and CX3CL1, in soft tissue sarcomas (STSs) and to assess the correlations between these levels as well as their correlations with clinicopathological data and the disease‐specific survival of STS patients. The mRNA levels of CCL2, CCL7 and CX3CL1 were analyzed in tumor tissues from 126 STS patients using qPCR. Low mRNA expression of CCL2 and CX3CL1 was significantly correlated with a worse prognosis (RR = 1.98; p = 0.019 and RR = 2.10; p = 0.014; multivariate Cox's regression analysis). A combined low expression of CCL2 and CX3CL1 was associated with a significantly increased risk of tumor‐related death as compared to patients with high expression levels of both chemokines (RR = 3.08; p = 0.003). A gender‐specific multivariate analysis revealed that female STS patients with low CX3CL1 mRNA expression had a 3.46‐fold increased risk of death (p = 0.004). Low expression of both CCL2 and CX3CL1 mRNAs resulted in an additive 5.37‐fold increased risk of tumor‐related death (p = 0.003) as compared to those with high expression of both parameters in female patients. In conclusion, this is the first study to show a significant correlation between combined low expression of CCL2 and CX3CL1 and a poor prognosis for STS patients, particularly in female patients.